Linking Agricultural Innovations to Knowledge Sharing in Africa - World Bank (World Bank, Washington, DC, 2012)
Most recent African indigenous knowledge (IK) literature, especially in agriculture, emphasizes that Africans are informed innovators. This literature is filled with success stories; excellent examples of local innovations and discoveries include crop breeding, grafting against pests, water harvesting, soil management, conservation and processing. Indigenous agricultural innovations have continued to be important as most of the locally-grown food is for local consumption.